Exploratory Data Analysis in Schools: A Logic Model to Guide Implementation - Courtney, Matthew B. (International journal of education policy and leadership, 2021)
Exploratory data analysis (EDA) is an iterative, open-ended data analysis procedure that allows practitioners to examine data without pre-conceived notions to advise improvement processes and make informed decisions. Education is a data-rich field that is primed for a transition into a deeper, more purposeful use of data. This article introduces the concept of EDA as a necessary structure to be embedded in school activities by situating it within the literature related to data-driven decision making, continuous school improvement systems, and action research methodologies. It also provides a succinct six-part framework to guide practitioners in establishing EDA procedures.